Pengaruh Dukungan Organisasi dan Work Value Terhadap Komitmen Organisasi Karyawan Generasi Y - Fahri, Syahrul; Mariatin, Emmy; Zahreni, Siti (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2017)
The aim of this research is to know the influence of Organizational Support Influence and Work Value towards Organizational commitment of the Y Generation Workers. The measurent used in this researce is the organization commitment scale and the work value scale. This research involves 211 workers in the Y generation in the Sakit Sari Mutiara Hospital Medan. The implication of this research hopes that organization should offer honors and or positive attitudes towards the Y generation, so that the workers’ organization support perception of the generation Y will show increase and improvement, with this increase perception given towards of the organization support the Y generation will enhance their affective commitment, continuance commitment and normative commitment.